ETHICAL SENSITIVITY OF ASPIRING BUSINESS LEADERS: Indian Context - Chully, Arun (2020)
Ethical business leaders can make a huge impact in creating flourishing communities in today’s world where Corporations are immensely powerful. In the business context, the first step of ethical decision-making is recognising the ethical dimension of a business problem itself, ethical sensitivity. This study investigates the impact of ethics education in the business program as well as role of early education environment in influencing the ethical sensitivity of business students. It was found that both these variables have significant impact in the ethical sensitivity of the participants of the study. The research has implications in revisiting the ethics education in universities and the role of early education environment in developing ethical business leaders for the sustainable future of our country.
Keywords: Business; Ethical Sensitivity; Ethics Programs; Leadership; University Education; Whole-Person Education